2011
DOI: 10.1002/ardp.201000327
|View full text |Cite
|
Sign up to set email alerts
|

Does One Keto Group Matter? Structure‐Activity Relationships of Glycyrrhetinic Acid Derivatives Modified at Position C‐11

Abstract: Several triterpenoic acids display a remarkable cytotoxicity on tumor cells. Glycyrrhetinic acid - the main content of the licorice root - possesses an apoptotic effect on tumor cells. Previous studies pointed out the presence of a keto group at position C-11 in glycyrrhetinic acid derivatives as the main reason for its apoptotic activity. Several pairs of derivatives were synthesized differing only at position C-11. These compounds were tested in a sulforhodamine B colorimetric assay for cytotoxicity screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Of these compounds, 28 , which possesses a methyl ester group, was the most active, with a MIC value that was 5-fold lower than that of the positive control. Csuk et al found no direct relationship between the C-11 ketone group and the apoptotic activity of compound 1 derivatives . However, in the present study, a significant difference in bacterial inhibition activity was observed between the 11-oxo and 11-deoxo compounds.…”
Section: Resultscontrasting
confidence: 76%
“…Of these compounds, 28 , which possesses a methyl ester group, was the most active, with a MIC value that was 5-fold lower than that of the positive control. Csuk et al found no direct relationship between the C-11 ketone group and the apoptotic activity of compound 1 derivatives . However, in the present study, a significant difference in bacterial inhibition activity was observed between the 11-oxo and 11-deoxo compounds.…”
Section: Resultscontrasting
confidence: 76%
“…Recently, GA attracted the focus of research interests not only for it can be accessed abundantly from the roots of licorice [up to 24% (7,8)], but also for its triggering apoptosis on tumor cells (9)(10)(11)(12). However, GA has only weak inhibitory effect against various tumor cell lines (IC 50 is approximately 80 lM), and some structural modifications have been previously performed (13)(14)(15)(16)(17)(18)(19)(20). We also become interested in producing more active GA analogs.…”
mentioning
confidence: 99%
“…The studies on structural modifications at ring-C were mainly focused on the carbonyl function located at C-11. According to Fiore and Salvi [ 48 , 49 ], a ketone group at position C-11 was the primary cause for the apoptotic activity of GA derivatives, but the research conducted by Csuk et al [ 50 ] showed that there was no direct relation between the presence of the C-11 ketone group and the apoptotic activity of the compounds. Also, esterification at C-30 was important, as mentioned above.…”
Section: Four Aspects Of the Structural Modifications Of Glycyrrhementioning
confidence: 99%